Wujud Prinsip Kerja Sama dalam Penyidikan Antara Penyidik dan Tersangka di Polsek Paciran Kabupaten Lamongan - Tri Lestari, Laila (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2015)
The study was aimed to describe the result of the study on analytical form of the cooperation principle in investigations between the investigator and suspect at the police station Paciran - Lamongan in terms of the cooperation principle form based on the maxim of quality, maxim relationships in the investigation between the investigator and suspect, and the maxim of quantity in the investigation between the investigator and suspect at the police station Paciran - Lamongan based on the Grice theory.